Readiness of Inclusive Tertiary Education Institutions for Preparing Students of Determination for Employment in the UAE - AL-BUKHARI, HALA ABDULLAH (2024)
The study aimed to identify the extent of readiness of inclusive higher education institutions to prepare students with determination to join the work-force of the United Arab Emirates. The research community consisted of administrators, service providers, faculty members, students with disabilities, and parents. The study sample included (150) individuals from the community. The researcher adopted the mixed approach using both the questionnaire and the interview as tools for the study. The researcher found out that majority of the sample believed there were institutions that are ready to prepare students with learning difficulties to work in the labour market. The results also showed that despite the existence of several procedures, laws, and regulations provided by the Emirates, there was a gap in the mechanisms for implementing these laws and regulations. In addition, the results showed that there were many requirements that institutions seek to implement represented in providing all the needs of students with disabilities, not just material needs. The study recommends many recommendations, the most important of which are: providing sufficient financial resources to implement integration programs and provide the necessary services to students with disabilities, developing policies that support integration at the national and institutional levels, and establishing specialized centers to provide support and training for students with disabilities.